Get detailed and reliable answers to your questions with IDNLearn.com. Ask your questions and get detailed, reliable answers from our community of knowledgeable experts.
Sagot :
Answer:
- 1
Step-by-step explanation:
Substitute a = - 1 into the expression, that is
(- 1)³ - 2(- 1)² + 3(- 1) + 5
= - 1 - 2(1) - 3 + 5
= - 1 - 2 - 3 + 5
= - 6 + 5
= - 1
Answer:
=(-1)³-2(-1)²+3(-1)+5
=-1-2(1)+3(-1)+5
=-1-2+3+5
=-3+8
=5
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and see you next time for more reliable information.